Teaching sex education through parents and the learning needs of the children - S Kritcharoen; K Phol-in; T Ingkathawornwong; J Srithaweewat (Journal of Health Science and Medical Research (JHSMR), 2008)
Objectives: To explore the levels of sex education provided by parents for their children and the learning needs of children; and to compare sex teaching styles between fathers and mothers; differing needs for sex education between sons and daughters and the sex education taught by parents and sex education learned by children. Research Design: Descriptive research Material and Method: Four hundred high school students and four hundred parents in Pattalung and Songkhla province were selected to participate. Data were collected using a questionnaire. The content validity for the sex education teaching by parents and the learning needs of their children was tested using Cronbach’s alpha coefficient, yielding values of 0.98 and 0.96 respectively. Descriptive statistics and t-test were used for data analysis. Results: The mean scores of the parents’ sex teaching and children’s learning needs were moderate (X=1.79, SD=0.70 and X =1.94, SD=0.52 respectively), scale 0-3 the difference between the mean score of the father’s and mother’s sex teaching and between their sons’ and daughters’ sex learning needs were statistically significant (p < 0.01, p < 0.001 respectively). The difference between the mean score of parents’ sex teaching and their children’s sex learning needs was also statistically significant (p < 0.01). Conclusion: The findings suggest that health care teams, and other relevant people should engage in activities to develop parent’s abilities for providing sex education for their children’s sex education needs.